Human rights protections and HIV prevalence among MSM who sell sex: cross-country comparisons from a systematic review and meta-analysis - Oldenburg, Catherine; Bärnighausen, Till (Global public health, 2016)
Laws and policies can affect the HIV risk of key populations through a number of direct and indirect pathways. We investigated the association between HIV prevalence among men who engage in transactional sex and language in the penal code protecting sexual minorities, including men who have sex with men (MSM), and sex workers. HIV prevalence among men who engage in transactional sex was assessed through meta-analysis of published literature and country surveillance reports. Meta-regression was used to determine the association between HIV prevalence and protective laws for sexual minorities and sex workers. Sixty-six reports representing 28 countries and 31,924 individuals were included in the meta-analysis. Controlling for multiple study- and country-level variables, legal protection for sexual minorities was associated with a 10.9% (95% CI: 3.8-18.0%) and sex workers associated with a 7.0% (95% CI: 1.3-12.8%) decrease in country-level HIV prevalence among men who engage in transactional sex. Laws that seek to actively protect sex workers and MSM may be necessary to decrease HIV risk for this key population.